Impact the some Antibiotics on Gene Expression Efflux Pump of Klebsiella pneumoniae Isolated from Clinical Sources - Hamady, Douaa Rashed; Abdullah, Rana Mujahid (Iraqi Journal of Science, 2026)
One hundred thirty bacterial samples were collected from different clinical sources, including (diuresis, sputum, wounds, blood, and burns) from different hospitals in Baghdad, including Imamain Al-Kadhimain (PBUT) Medical City, Al-Karkh General Hospital, Al-Kadhimiya Children’s Hospital, The burns Hospital, Ghazi Al Hariri Hospital and Baghdad Hospital. The isolates were diagnosed with phenotypic, microscopic, and biochemical tests, and molecular diagnosis was performed by detecting the 16SrRNA gene. After the final diagnosis, 50/130 (38.4%) of K. pneumoniae bacteria were obtained. The results of the study showed that the highest percentage of isolation of K. pneumoniae bacteria was from sputum samples of patients, which amounted to 14/60 (46.67%), followed by 25/60 (41.67%) of urine, 2/5 (40%) of burns, 6/20 (30%) of wounds and 3/15 (20%) of blood. A pattern of multi-drug resistance (MDR) was found among all K. pneumoniae isolates at 34 (68%). The results of the statistical analysis showed highly significant differences (p≤0.001) between most of the treatments studied for gene folding in resistant isolates, and of the treatment with the antibiotic ceftazidime was recorded the highest folding of acrAB, gene was (4.88±2.73), followed by the combination of the antibiotics ceftazidime + gentamicin together, in mdtK gene (4.52±0.92). The other treatments recorded increased and decreased in folding, but it was not significant (p>0.05).